Influence of sulphur and potassium levels on yield and yield attribute of sesame (Sesamum indicum L.) - Ahmad, Farhan; Ahmad, Junaid; Nawaz, Haq; Abbas, Muhammad Waseem; Shah, Minhaj Ali; Iqbal, Sarmad; Mehmood, Zahid; Ali, Mehran (Research in Agriculture Livestock and Fisheries, 2018)
A field experiment on influence of sulphur and potassium levels on yield and yield attributes of sesame was conducted in Agronomy Research Farm, University of Agriculture Peshawar, Khyber Pakhtunkhwa (KP) during Kharif season, 2017. Varying levels of sulphur (0, 25, 50 and 75 kg ha-l) and potassium (0, 25, 50 and 75 kg ha-l) were applied to experimental plots. The results revealed that sesame significantly responded to the application of sulphur and potassium up to 50 kg ha-l for growth, quality, yield and yield attributes of sesame. The taller plant (76.83 cm), maximum number of branches per plant (3.87), more number of capsules per plant (43.82), more number of seeds per capsules (59.36), maximum seed yield (673 kg ha-1), maximum stover yield (1078 kg ha-1), more oil content (48.76 %) and maximum oil yield (291.7 kg ha-1) were noticed where 50 kg ha-1 sulphur treated. On the contrary taller plant (76.97 cm), maximum number of branches per plant (3.93), more number of capsules per plant (42.77), more number of seeds per capsules (59.36), maximum seed yield (617 kg ha-1), maximum stover yield (1043 kg ha-1), more oil content (48.65 %) and maximum oil yield (286.6 kg ha-1) were recorded from 50 kg ha-1 potassium treatments. Res. Agric., Livest. Fish.5(2): 147-150, August 2018